2019
DOI: 10.1016/j.heliyon.2019.e01240
|View full text |Cite
|
Sign up to set email alerts
|

Stapling cartridge lavage cytology in limited resection for pulmonary malignant tumors: assessment of cytological status of the surgical margin

Abstract: Introduction Sublobar resection in primary lung cancer and pulmonary metastatic tumor can result in recurrence at the surgical margin. Confirming the absence of tumor cells at the cut-end is important. We sought to evaluate the efficacy of intraoperative lavage cytology (ILC) of autostapling cartridges in preventing local failure. Materials and methods An intraoperative cytology examination was performed in 262 consecutive patients undergoing wedge or segmental resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…As for segmentectomy, excluding the three patients who underwent palliative resection, the CT images and postoperative pathology of the other nine patients showed higher tumor malignancy than the three patients who underwent wedge resection. This is also in line with the view of some researchers that the malignancy of the first lung tumor is proportional to the recurrence probability after sublobar resection ( 12 , 16 ). Additionally, some researchers have suggested that defects in intraoperative frozen pathology techniques may be a major reason for recurrence at surgical margins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As for segmentectomy, excluding the three patients who underwent palliative resection, the CT images and postoperative pathology of the other nine patients showed higher tumor malignancy than the three patients who underwent wedge resection. This is also in line with the view of some researchers that the malignancy of the first lung tumor is proportional to the recurrence probability after sublobar resection ( 12 , 16 ). Additionally, some researchers have suggested that defects in intraoperative frozen pathology techniques may be a major reason for recurrence at surgical margins.…”
Section: Discussionsupporting
confidence: 91%
“…The maximum standardized FDG uptake value (SUVmax) of the mass on the lungs of these patients and the CT value of the mass were recorded by enhanced CT. At the same time, the patient’s medical history was collected before and after the pathological results of the patient’s first operation. Patients with a tumor diameter >2.0 cm, solid tumor, presence of vascular invasion or lymphatic infiltration, visceral pleural invasion, or tumor spread through air spaces (STAS) were defined as high risk ( 16 ). The specific surgical methods, surgical sites, and other data were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…We routinely performed irrigation of any cartridges used in pulmonary stapling to make a rapid cytological diagnosis of surgical stump positivity. 14 We generally make additional resection if the irrigation cytology was positive.…”
Section: Methodsmentioning
confidence: 99%
“…We routinely performed irrigation of any cartridges used in the pulmonary stapling in order to make a rapid cytological diagnosis for surgical stump positivity (7). After intraoperative CT, the specimen was instilled with 10% formalin neutral buffer solution using a 23-G needle and then soaked in the solution for 48 h. After removing the stapler needles from the staple line, the specimen was cut into pieces for macroscopic and microscopic evaluations of the tumor diameter and surgical margin.…”
Section: The Pathological Assessmentmentioning
confidence: 99%